PERBANDINGAN KARAKTER TANGGUNG JAWAB SISWA KELAS XII IPA DENGAN XII IPS SMAN 1 PERANAP KABUPATEN INDRAGIRI HULU - Yurika, Wanda; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study was conducted with the aim to determine the level of comparison of the character of the responsibility of the XII IPA 1 grade students, the character of the responsibility of XII IPS class students at SMAN 1 Peranap, and to compare the characters' responsibilities of XII IPA students with XII IPS SMAN 1 Peranap. Po in this study amounted to 200 students with a sample of 100 students namely students of class XII IPA 50 people and students of class XII IPS 50 people using simple random sampling technique. Data collection techniques used descriptive quantitative analysis using descriptive data analysis and two samples of different test samples. separate with the help of SPSS version 21. The results of the study show that from the calculation of the percentage of respondents it was found that the level of character of the responsibility of the XII IPA students was very high, as evidenced by the acquisition of 85.6%. While the character of the responsibility of Social Sciences XII students is also very high, it is proven that the acquisition is as much as 80.9%. From the results of the T Test based on SPSS version 21 that there are differences in the character of the responsibility of students of class XII IPA with XII IPS SMAN 1 Peranap, evidenced by (sig) 0.041 <0.05 and T count 2.072 greater than t table 1.98447.Key Words: Characters Responsibility